2017
DOI: 10.1097/pec.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Epilepsy Successfully Treated With Daily Clobazam

Abstract: Hot water epilepsy (HWE) is a rare form of reflex epilepsy precipitated by a bath or shower in hot water. Although the condition is benign and a decreased bath temperature will help, antiepileptic drugs may be needed in some cases. Prophylactic clobazam is currently the first choice treatment option. Here we report the case of a 10-year-old boy with HWE successfully treated with daily doses of clobazam. Daily clobazam was preferred over prophylactic clobazam because of the patient's frequent bathing and parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…16,27 In another study, however, seizures were brought under control with daily clobazam use. 28 Lowering the water temperature and modifying bathing habits were not effective in our cases. We started all our HWE cases on continuous or prophylactic antiepileptic drugs since reflex seizures persisted despite routine precautions.…”
Section: Discussionmentioning
confidence: 61%
“…16,27 In another study, however, seizures were brought under control with daily clobazam use. 28 Lowering the water temperature and modifying bathing habits were not effective in our cases. We started all our HWE cases on continuous or prophylactic antiepileptic drugs since reflex seizures persisted despite routine precautions.…”
Section: Discussionmentioning
confidence: 61%
“…We found that early prophylactic treatment with oral benzodiazepines prior to taking the hot water bath successfully prevents the occurrence of these seizures [20]. Many other investigators have also confirmed the therapeutic effectiveness of clobazam [21].…”
mentioning
confidence: 51%
“…Clobazam is a novel option for preventing and seems to be an appropriate choice. [16][17][18] Most reports of HWE are from India and Turkey, suggesting a genetic predisposition. A genetically aberrant thermoregulatory system or an anatomical abnormality of the temporo-insular and parietal networks has been suggested as a possible mechanism for epiloptogenesis.…”
Section: Highlightmentioning
confidence: 99%